2021
DOI: 10.5498/wjp.v11.i12.1407
|View full text |Cite
|
Sign up to set email alerts
|

Psychoeducation in bipolar disorder: A systematic review

Abstract: BACKGROUND Bipolar disorder (BD) is a severe psychiatric disorder characterized by mood swings. Psychosocial interventions, such as psychoeducation, play an essential role in promoting social rehabilitation and improving pharmacological treatment. AIM To investigate the role of psychoeducation in BD. METHODS A systematic review of original studies regarding psychoeducation interventions in patients with BD and their relatives was developed. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…Psychoeducation is an intervention strategy based on providing patients and/or relatives with information about the disorder to enhance their understanding and enable early identification of warning signs and mood changes, improving treatment adherence [47]. In a review, Rabelo et al [48] showed positive effects of the psychoeducational intervention on both patients and family members in bipolar disorders. According to the authors, psychoeducation as an adjunct strategy to pharmacotherapy leads to a reduction in the frequency of new mood episodes, length of hospital stay, and adherence to drug therapy.…”
Section: Psychoeducationmentioning
confidence: 99%
“…Psychoeducation is an intervention strategy based on providing patients and/or relatives with information about the disorder to enhance their understanding and enable early identification of warning signs and mood changes, improving treatment adherence [47]. In a review, Rabelo et al [48] showed positive effects of the psychoeducational intervention on both patients and family members in bipolar disorders. According to the authors, psychoeducation as an adjunct strategy to pharmacotherapy leads to a reduction in the frequency of new mood episodes, length of hospital stay, and adherence to drug therapy.…”
Section: Psychoeducationmentioning
confidence: 99%
“…Several studies revealed that psychoeducation is more helpful among patients with manic symptoms of BD. As these patients learn early features of manic episodes, substantial improvements are achieved in socialization and employment [120][121][122]. Psychoeducation combines cognitive-behavioral therapy, group therapy, and education intervention [123,124].…”
Section: Role Of Psychotherapy In Bipolar Mood Disordermentioning
confidence: 99%
“…Psychoeducational interventions are an intervention strategy that combines psychological counseling and education to provide patients and/or family caregivers with education in relevant subject areas to enhance their understanding and support, learn to recognize warning signs and mood changes early, and improve treatment compliance [ 26 , 27 ]. Psychoeducational interventions that provide information, education, and psychological support to patients and/or their informal caregivers, such as gynaecological cancer [28] , adolescent hyperactivity [29] , and stroke [30] , are effective and have been systematically assessed.…”
Section: Introductionmentioning
confidence: 99%